HISTORY OF WAHBAH AL-ZUHAYLI THOUGHT - M. Doni; Sofia Ridha (Adisam Publisher, 2025)
This research aims to examine the history of Wahbah al-Zuhayli's thought as one of the great contemporary scholars who contributed significantly to the development of modern Islamic law. The focus of the study is directed at the educational background, intellectual development, main works, and methodological character of his thinking in the field of fiqh, fiqh proposals, and moderation of Islamic law. This research uses a qualitative method with a type of library research and a historical-philosophical approach to trace the dynamics of al-Zuhayli's thought in the historical and social context of his time. Data were obtained from Wahbah al-Zuhayli's primary works as well as relevant secondary literature, then analyzed descriptive-analytically. The results of the study show that Wahbah al-Zuhayli's thought is rooted in the classical fiqh tradition but is developed contextually through the approach of moderation (wasathiyah), maqasid al-shariah, and comparative fiqh. This approach makes him able to bridge the gap between the nash shar'i and modern social reality without being trapped in sectarian fanaticism or legal liberalism. The findings of this study confirm that Wahbah al-Zuhayli's contribution is not only important in the academic realm, but also has major implications for strengthening religious moderation, the development of contemporary fiqh, and the application of Islamic law that is adaptive and oriented to the benefit of the ummah, including in the context of Islam in Indonesia.